Studies of the Rate Constant of L-DOPA Oxidation and Decarboxylation by HPLC - Zhou, Y.; Alany, R.; Chuang, Victor; Wen, J. (Fried. Vieweg & Sohn Verlagsgesellschaft, 2012)
The objective of current investigation was to study the degradation behavior of L-DOPA under different conditions by high performance liquid chromatography (HPLC), and to develop and validate a stability-indicating HPLC method. The developed RP-HPLC method was validated with respect to linearity, accuracy, precision and specificity. Oxidation was found to occur in alkaline and to some extent in thermal conditions, while the drug was stable when incubated at acidic conditions and under photolytic stress. The oxidation of L-DOPA was observed to follow first-order kinetics. The degradation rate constants and half-life were calculated. The cytotoxicity and enzymatic degradation of L-DOPA was examined using the human intestinal epithelial Caco-2 cells. The drug was rapidly decarboxylated by aromatic amino acid decarboxylase to dopamine. The conversion of L-DOPA to dopamine was dose - and time-dependent.